1995
DOI: 10.1002/ijc.2910610306
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus and cervical intraepithelial neoplasia grade II‐III: A population‐based case‐control study

Abstract: The association between certain human papillomaviruses (HPV) and cervical intraepithelial neoplasia (CIN) is well documented, but there is uncertainty about the strength of association and the role of co-factors is unclear. This population-based case-control study in Norwegian women 20-44 years of age included 103 cases with histologically confirmed CIN II-III and 234 age-matched and randomly selected controls. Cytological specimens from the cervix were analyzed using the polymerase chain reaction (PCR). In al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
40
1
2

Year Published

1995
1995
2000
2000

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 69 publications
(47 citation statements)
references
References 19 publications
4
40
1
2
Order By: Relevance
“…It is of interest that smoking was no longer a risk factor of CIN after adjustment for HPV infections as in several recent studies (Schiffman et al, 1993;Olsen et al, 1995). Other lines of research have documented smoking as a risk factor for high-grade CIN (Kjaer et al, 1998;Olsen et al, 1998), and the present data do not rule out the possibility that smoking is a risk factor for CIN progression.…”
Section: Discussionmentioning
confidence: 42%
“…It is of interest that smoking was no longer a risk factor of CIN after adjustment for HPV infections as in several recent studies (Schiffman et al, 1993;Olsen et al, 1995). Other lines of research have documented smoking as a risk factor for high-grade CIN (Kjaer et al, 1998;Olsen et al, 1998), and the present data do not rule out the possibility that smoking is a risk factor for CIN progression.…”
Section: Discussionmentioning
confidence: 42%
“…Aunque algunos estudios en Latinoamérica notifican que el riesgo relativo de las mujeres a padecer cáncer cervical aumentó en relación inversa al número de años de educación, 25 en el presente estudio y en otros realizados en diversas áreas, dicha relación no fue estadísti-camente significativa. 26 En este estudio y en coincidencia con lo que notifica al respecto la SSA, 27 las mujeres con más de siete embarazos representan más de 40%, hecho que posiblemente influye en los hallazgos, pues se observa una tendencia lineal de riesgo a partir del primer embarazo, de modo tal que el riesgo de las mujeres con 12 o más embarazos fue cinco veces mayor. Una probable explicación se fundamenta en el hecho de que el embarazo provoca un estado de inmunosupresión que podría aumentar la susceptibilidad del organismo a los agentes infecciosos.…”
Section: Discussionunclassified
“…The epidemiological data supporting this assertion include reports that HPV DNA can be recovered from over 95% of all cervical tumours (Bosch et al, 1995;Walboomers et al, 1999;Cuzick et al, 2000), and that women infected with oncogenic HPV types have relative risks of 40-180 for the development of high-grade cervical disease (IARC, 1995;Olsen et al, 1995). Additionally, molecular studies have identified mechanisms by which high-risk HPV types contribute to carcinogenesis.…”
mentioning
confidence: 98%